Esophageal ultrasound (EUS) assessment of T4 status in NSCLC patients. (December 2017) - Kuijvenhoven, Jolanda C.; Crombag, Laurence; Breen, David P.; van den Berk, Inge; Versteegh, Michel I.M.; Braun, Jerry; Winkelman, Toon. A.; van Boven, Wimjan; Bonta, Peter I.; Rabe, Klaus F.; Annema, Jouke T.
Highlights: Lungtumors positioned adjacent to the esophagus can be visualised by EUS (B). EUS imaging can assess the presence or absence of mediastinal tumor invasion. EUS provides important additional staging information complementary to CT findings. T4 assessment by EUS (B) should be considered following an EBUS nodal examination. Abstract: Background: Mediastinal and central large vessels (T4) invasion by lung cancer is often difficult to assess preoperatively due to the limited accuracy of computed tomography (CT) scan of the chest. Esophageal ultrasound (EUS) can visualize the relationship of para-esophageally located lung tumors to surrounding mediastinal structures. Aim: To assess the value of EUS for detecting mediastinal invasion (T4) of centrally located lung tumors. Methods: Patients who underwent EUS for the diagnosis and staging of lung cancer and in whom the primary tumor was detected by EUS and who subsequently underwent surgical- pathological staging (2000–2016) were retrospectively selected from two university hospitals in The Netherlands. T status of the lung tumor was reviewed based on EUS, CT and thoracotomy findings. Surgical- pathological staging was the reference standard. Results: In 426 patients, a lung malignancy was detected by EUS of which 74 subjects subsequently underwent surgical- pathological staging. 19 patients (26%) were diagnosed with stage T4 based on vascular (n = 8, 42%) or mediastinal (n = 8, 42%) invasion or both (n = 2, 11%), one patient (5%) had vertebral involvement. Sensitivity, specificity, PPV and NPV for assessing T4 status were: for EUS (n = 74); 42%, 95%, 73%, 83%, for chest CT (n = 66); 76%, 61%, 41%, 88% and the combination of EUS and chest CT (both positive or negative for T4, (n = 34); 83%, 100%, 100% 97%. Conclusion: EUS has a high specificity and NPV for the T4 assessment of lung tumors located para-esophageally and offers further value to chest CT scan.